6d(d-9)=0

Simple and best practice solution for 6d(d-9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6d(d-9)=0 equation:


Simplifying
6d(d + -9) = 0

Reorder the terms:
6d(-9 + d) = 0
(-9 * 6d + d * 6d) = 0
(-54d + 6d2) = 0

Solving
-54d + 6d2 = 0

Solving for variable 'd'.

Factor out the Greatest Common Factor (GCF), '6d'.
6d(-9 + d) = 0

Ignore the factor 6.

Subproblem 1

Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0

Subproblem 2

Set the factor '(-9 + d)' equal to zero and attempt to solve: Simplifying -9 + d = 0 Solving -9 + d = 0 Move all terms containing d to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + d = 0 + 9 Combine like terms: -9 + 9 = 0 0 + d = 0 + 9 d = 0 + 9 Combine like terms: 0 + 9 = 9 d = 9 Simplifying d = 9

Solution

d = {0, 9}

See similar equations:

| =9m-4-8n | | 3x+96=X+44 | | 5q(4q-3)=0 | | 11+(-7)-7-9= | | 9x+90=3x+18 | | 5.20/.75 | | 11+(7)7-9= | | x*7-7=-8 | | 121x^2+20=0 | | -3(x-9)=-7x+7 | | 6x-6y=120 | | (3k-8)(k-3)=0 | | 6*6=x*8 | | 360-(116+5x-147+2x)=y | | 12.25+0.13x=12.75-0.11x | | x=6x-1/3 | | 15/7.5xN=12/6x5 | | z*10-4=9 | | 3n(n+9)=0 | | 13x-4x+8= | | 7*10-4=9 | | 6v+15=9(v+3) | | (10+2)=5(10+8) | | 6v+15=9 | | (8m+3)(m-3)=0 | | 4x+6y=943 | | 36-25x=-144 | | 2(v+4)=7v+13 | | t*3-2=16 | | (3x/5)=(1/4) | | a*4+5=12 | | 9x-25=2x+52 |

Equations solver categories